2010
DOI: 10.1051/0004-6361/200913963
|View full text |Cite
|
Sign up to set email alerts
|

Solar near-relativistic electron observations as a proof of a back-scatter region beyond 1 AU during the 2000 February 18 event

Abstract: Aims. We study the near-relativistic (NR; >30 keV) electron event observed on 2000 February 18 by near-Earth spacecraft. Previous works have explained this event by assuming that the propagation of NR electrons is essentially "scatter-free" at heliocentric radial distances r < 1 AU, and that beyond 1 AU particles are "back-scattered" by magnetic field irregularities. Methods. Our aim is to re-visit this interplanetary propagation scenario and infer the injection profile at the Sun by fitting the electron direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
3
5
0
Order By: Relevance
“…The first IP shock marked in the right panel of Figure 5, observed in situ by STEREO-B on November 2, 22:08 UT, could provide the structure acting as a reflecting barrier located beyond STEREO-B at the time of the SEP event onset. This structure may create the appropriate conditions to mirror energetic particles back to the observer in sunward direction, as previously suggested by different authors (Anderson et al 1995;Bieber et al 2002;Malandraki et al 2002;Roelof 2008;Tan et al 2009;Agueda et al 2010;Klassen et al 2012). Note that this reflecting boundary may have also contributed to the observation of sunward-directed particles by MESSENGER.…”
Section: Energetic Particle Anisotropiessupporting
confidence: 65%
See 1 more Smart Citation
“…The first IP shock marked in the right panel of Figure 5, observed in situ by STEREO-B on November 2, 22:08 UT, could provide the structure acting as a reflecting barrier located beyond STEREO-B at the time of the SEP event onset. This structure may create the appropriate conditions to mirror energetic particles back to the observer in sunward direction, as previously suggested by different authors (Anderson et al 1995;Bieber et al 2002;Malandraki et al 2002;Roelof 2008;Tan et al 2009;Agueda et al 2010;Klassen et al 2012). Note that this reflecting boundary may have also contributed to the observation of sunward-directed particles by MESSENGER.…”
Section: Energetic Particle Anisotropiessupporting
confidence: 65%
“…Under the assumptions of the model, the best fit for STEREO-B observations is obtained for λ r = 1.2 AU, requiring also an extended injection close to the Sun starting around 23:10 UT and with intensity levels much lower than STEREO-A. The model fails to reproduce the high intensities measured by the antisunward-pointing telescope, supporting the idea of the presence of a reflecting barrier located beyond the s/c, which has not been included in the simulation (see Agueda et al 2010).…”
Section: Interplanetary Transport Simulationsmentioning
confidence: 90%
“…In total, the duration of this peak at FWHM was 13 min, which is longer than the duration of the main peak (9 min). Similar impulsive events exhibiting a separate peak of inward streaming electrons were discussed in papers by Agueda et al (2010) and Wang et al (2011). They have concluded that a reflecting boundary was located at a distance of ≥0.2-1.7 AU along the magnetic field line beyond the Earth.…”
Section: Observationssupporting
confidence: 53%
“…Agueda & Klein (2013) analyzed one of the events in this sub-sample, occurring on 1998 April 20. The changes in the topology of the PADs may be related to flux tube variations or could be due the global scenario for these events, which was more complicated than the one assumed in the interplanetary transport model used in this study (see Agueda et al 2010;Kartavykh et al 2013, for additional examples). We discarded these four events from further analysis.…”
Section: Event Selectionmentioning
confidence: 99%